2008
DOI: 10.1007/s11483-008-9083-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fish Gelatin at Nanoscale Using Atomic Force Microscopy

Abstract: Atomic force microscopy (AFM) was used as a meaningful tool to characterize the nanostructure of gelatin from catfish (Ictalurus punctatus) skin. The gelatins extracted with pretreatments including acid pretreatment, alkaline pretreatment, and alkaline followed by acid pretreatment (optimized extraction conditions). The resulting gelatins were imaged using AFM and their nanostructure was studied. The AFM images showed that gelatin extracted with acid pretreatment had a coacervate structure while with alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
4
11
0
1
Order By: Relevance
“…[5] Acid and alkaline pretreatment as well as extraction conditions affect both composition and distribution of hydrophobic amino acid of fish gelatin, and thereby influenced their physical properties. [6,7] Generally, mild acid pretreatment is used for gelatin production due to low concentration of intra-and inter-chain non-reducible crosslink in fish collagen and this process is sufficient to achieve adequate swelling and disruption of the non-covalent intra-and inter-molecular bonds. [8,9] Alkali, particularly lime, pretreatment of fish skins may reduce protein molecular size through slight hydrolysis of the polar regions and this facilitates lyotropic hydration or swelling of collagen protein by organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Acid and alkaline pretreatment as well as extraction conditions affect both composition and distribution of hydrophobic amino acid of fish gelatin, and thereby influenced their physical properties. [6,7] Generally, mild acid pretreatment is used for gelatin production due to low concentration of intra-and inter-chain non-reducible crosslink in fish collagen and this process is sufficient to achieve adequate swelling and disruption of the non-covalent intra-and inter-molecular bonds. [8,9] Alkali, particularly lime, pretreatment of fish skins may reduce protein molecular size through slight hydrolysis of the polar regions and this facilitates lyotropic hydration or swelling of collagen protein by organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…For perch skin gelatin, a fine gelatin surface had been observed when alkali and acid were used for pretreatment as compared to alkali pretreatment alone [28]. Spherical structures were also found in the AFM images of alkaline-acid pretreated catfish gelatin [29]. However, Yang and Wang [26] showed that in low concentrations to be correlated inversely to the gelatin molecular weight distribution [27].…”
Section: Micro/nano Structurementioning
confidence: 99%
“…Gelatin has a wide range of applications in the food, pharmaceutical and photographic industries, so understanding and then improving the physical properties of gelatin is important for increasing its utilisation. Yang and co‐workers26–29 have carried out a series of studies on the gelatin from catfish ( Ictalurus punctatus ) skin. Catfish gelatin molecules with annular pores and spherical aggregates were seen for the first time by them.…”
Section: Characterising the Macromolecular Nanostructure Of Agricultumentioning
confidence: 99%